2019
DOI: 10.1177/0734242x18815951
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment for solid waste management in Lebanon: Economic implications of carbon credit

Abstract: Solid waste management has witnessed much progress in recent years with considerable efforts targeting the reduction of associated impacts and carbon emissions. Such efforts remain relatively limited in developing economies due to inefficient management practices. In this study, a life cycle assessment (LCA) approach is adopted to identify integrated systems with minimal impacts and reduced emissions in a developing context coupled with an economic valuation and sensitivity analysis to assess the effect of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Most of the methane generated in a landfill is not captured resulting in high climate change and photochemical oxidant formation in SN-1 than in composting (SN-2) and anaerobic digestion (SN-3). Similar observations were indicated by Maalouf and El-Fadel [32], who indicated that methane emissions in a landfill are the major contributor for climate change and photochemical oxidant formation. Thus, diverting the organic waste fractions to composting or anaerobic digestion process would significantly reduce the climate change and photochemical oxidant formation.…”
Section: Resultssupporting
confidence: 87%
“…Most of the methane generated in a landfill is not captured resulting in high climate change and photochemical oxidant formation in SN-1 than in composting (SN-2) and anaerobic digestion (SN-3). Similar observations were indicated by Maalouf and El-Fadel [32], who indicated that methane emissions in a landfill are the major contributor for climate change and photochemical oxidant formation. Thus, diverting the organic waste fractions to composting or anaerobic digestion process would significantly reduce the climate change and photochemical oxidant formation.…”
Section: Resultssupporting
confidence: 87%
“… a Laceco/Ramboll (2012); Maalouf and El-Fadel (2019b). b Data retrieved from Di Maria and Micale (2013) for a typical Italian city. LB: Lebanon; IT: Italy. …”
Section: Methodsmentioning
confidence: 99%
“… a Laceco/Ramboll (2012); Maalouf and El-Fadel (2019b). …”
Section: Methodsmentioning
confidence: 99%
“…Without interventions, it is expected that existing open dumps will account for 10% of worldwide GHG emissions by 2025 (Law and Ross, 2019). However, studies (Maalouf and El-Fadel, 2018b, 2019) showed that substituting open dumping or burning with proper waste management systems such as engineered landfills coupled with a proper landfill gas collection system, incineration, recycling, biological treatment, food waste diversion, and/or energy recovery can contribute to significant savings in emissions that can reach up to 24–95% compared to the baseline, depending on the tested system. Another study by Maalouf et al (2019) reported that the increase in the source segregation intensity with proper management of residual MSW resulted in significant savings in the climate change impact (reaching up to 20%) and stratospheric ozone depletion potential (about 55%) in a developing economy.…”
Section: Introductionmentioning
confidence: 99%